Knowledge, attitude and practice regarding human papillomavirus vaccination among medical students - Chandila, Prerna; Kaur, Amrit Pal; Jyothi (International Journal of Research in Medical Sciences, 2025)
Background: Cervical cancer is a leading cause of cancer-related deaths among women, especially in developing countries like India. Human papillomavirus (HPV) types 16 and 18 are primary causative agents, and the HPV vaccine is a key preventive tool. However, uptake remains low due to limited awareness, safety concerns, and cultural misconceptions. This study aimed to evaluate knowledge, attitudes, and practices (KAP) regarding HPV vaccination among medical students and to identify barriers and facilitators to vaccine uptake. Methods: A cross-sectional study was carried out at a tertiary care teaching hospital in Amritsar India. Undergraduate students aged 18-22 years, from 1st, 2nd, 3rd and 4th year professional MBBS students were included in the study. Results: Out of 300 participants, 229 (76.33%) were aware of the HPV vaccine, while only 21 (7%) had received it. Common barriers included limited access, concerns over safety and efficacy, and cost. Demographic factors like age, gender, maternal education, and family history of malignancy showed no significant association with knowledge levels. A majority expressed willingness to get vaccinated in the future. Conclusions: Medical students in India demonstrate moderate knowledge of HPV vaccination. Improving education on vaccine safety and efficacy, incorporating it into the curriculum, increasing awareness programs, reducing costs, and introducing supportive government policies may enhance vaccine acceptance.